2022
DOI: 10.1186/s12876-022-02199-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined systemic immune-inflammatory index (SII) and prognostic nutritional index (PNI) predicts chemotherapy response and prognosis in locally advanced gastric cancer patients receiving neoadjuvant chemotherapy with PD-1 antibody sintilimab and XELOX: a prospective study

Abstract: Background Previous studies have confirmed that systemic immune-inflammatory index (SII) and prognostic nutritional index (PNI) can predict the prognosis and chemotherapy efficacy of various malignant tumors. However, to the best of our knowledge, no study investigated the SII combined with PNI score to predict the efficacy of anti-programmed death 1 (anti-PD-1) antibody sintilimab and XELOX regimen (capecitabine plus oxaliplatin) in the treatment of locally advanced gastric cancer. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…A high inflammatory response leads to the release of a series of inflammatory mediators from tumor cells, causing oxidative damage and DNA mutation, which in turn alters the tumor microenvironment and promotes the proliferation and migration of tumor cells ( 47 , 48 ). The systemic inflammatory response will aggravate malnutrition and decline in body function of patients with malignant tumors, which will promote poor prognosis of patients with malignant tumors ( 29 , 30 ). It has been reported that muscle hormones secreted by myocytes can inhibit the growth of tumor cells, and that muscle hormone expression may be reduced in sarcopenia, leading to tumor proliferation and recurrence ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A high inflammatory response leads to the release of a series of inflammatory mediators from tumor cells, causing oxidative damage and DNA mutation, which in turn alters the tumor microenvironment and promotes the proliferation and migration of tumor cells ( 47 , 48 ). The systemic inflammatory response will aggravate malnutrition and decline in body function of patients with malignant tumors, which will promote poor prognosis of patients with malignant tumors ( 29 , 30 ). It has been reported that muscle hormones secreted by myocytes can inhibit the growth of tumor cells, and that muscle hormone expression may be reduced in sarcopenia, leading to tumor proliferation and recurrence ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral venous blood was collected from all patients on an empty stomach within 1 week before surgery. Peripheral blood neutrophil, lymphocyte, and platelet counts in LAGC patients were analyzed by the method in our previous study ( 29 , 30 ). The specific operation process is as follows: using an automatic hematology analyzer (Beckman Coulter LH750) to measure and analyze the counts of neutrophils, platelets and lymphocytes, and the albumin level using an automatic hematology analyzer (Beckman Coulter AU5800) assay analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the tumor-node-metastasis (TNM) staging system is currently the most authoritative tool for prognosis prediction, many indicators have been reported to play a role in predicting the short-term or long-term prognosis of gastric cancer patients, such as the neutrophil to platelet ratio (NPR) ( 6 ), red cell distribution width (RDW) ( 7 ), C-reactive protein to albumin ratio (CAR) ( 8 ), albumin to fibrinogen ratio (AFR) ( 9 ), prognostic nutritional index (PNI) ( 10 ), and systemic immune-inflammatory index (SII) ( 11 ). However, these parameters are not widely applied in clinics due to the disadvantages of instability and large differences in baseline values.…”
Section: Introductionmentioning
confidence: 99%